Reflectance aptasensor based on metal salphen label for rapid and facile determination of insulin - Taib, Mahirah; Tan, Ling Ling; Abd Karim, Nurul Huda; Goh, Choo Ta; Lee, Yook Heng; Khalid, Bahariah (Elsevier, 2020)
An optical aptasensor-based sensing platform for rapid insulin detection was fabricated. Aminated porous silica microparticles (PSiMPs) were synthesized via a facile mini-emulsion method to provide large surface area for covalent immobilization of insulin-binding DNA aptamer (IGA3) by glutaraldehyde cross-linking protocol. A Nickel-salphen type complex with piperidine side chain [Ni(II)-SP] was synthesized with a simple one-pot reaction, and functionalized as an optical label due to strong π-π interaction between aromatic carbons of G-quadruplex DNA aptamer and planar aromatic groups of Ni(II)-SP to form the immobilized IGA3-Ni(II)-SP complex, i.e. the dye-labeled aptamer, thereby bringing yellow colouration to the immobilized G-quartet plane. Optical characterization of aptasensor towards insulin binding was carried out with a fiber optic reflectance spectrophotometer. The maximum reflectance intensity of the immobilized IGA3-Ni(II)-SP complex at 656 nm decreased upon binding with insulin as aptasensor changed to brownish orange colouration in the background. This allows optical detection of insulin as the colour change of aptasensor is dependent on the insulin concentration. The linear detection range of the aptasensor is obtained from 10 to 50 μIU mL−1 (R2 = 0.9757), which conformed to the normal fasting insulin levels in human with a limit of detection (LOD) at 3.71 μIU mL−1. The aptasensor showed fast response time of 40 min and long shelf life stability of >3 weeks. Insulin detection using healthy human serums with informed consent provided by participants suggests the DNA aptamer biosensor was in good agreement with ELISA standard method using BIOMATIK Human INS (Insulin) ELISA Kit.